2009
DOI: 10.1002/jmv.21499
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of occult hepatitis B cases in Greek blood donors

Abstract: The use of sensitive nucleic acid testing for hepatitis B virus in blood donors revealed a number of HBV DNA(+) cases among HBsAg(-) donors, a status known as occult HBV infection. The purpose of this study was the serological and molecular characterization of occult HBV infection in Greek blood donors. A prospective study was undertaken in order to identify occult HBV infection cases in blood donors. As part of the routine screening of blood donations in Greece, blood units were screened individually by a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 75 publications
(101 reference statements)
9
53
0
Order By: Relevance
“…32 Another amino acid substitution, T126I, which is unique to genotype C, has also been reported to affect the antigenicity of HBsAg. [33][34][35] T143S was invariably associated with T126I in this study, suggesting that amino acid substitutions (not T126I itself, but in combination with T143S) affect the antigenicity of HBsAg. In this study, T126I appeared in only HBV/B and was not specific to genotype C, in contrast to findings of a previous study.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…32 Another amino acid substitution, T126I, which is unique to genotype C, has also been reported to affect the antigenicity of HBsAg. [33][34][35] T143S was invariably associated with T126I in this study, suggesting that amino acid substitutions (not T126I itself, but in combination with T143S) affect the antigenicity of HBsAg. In this study, T126I appeared in only HBV/B and was not specific to genotype C, in contrast to findings of a previous study.…”
Section: Discussionmentioning
confidence: 79%
“…Because the T126I substitution involves the largest change in chemical properties, it is most likely to cause structural changes in HBsAg. [33][34][35] In addition, A1762T/G1764A was observed in only one child, who had recovered from wildtype HBV infection. Although previous studies have reported A1762T/G1764A mutations in occult HBV infection, [11][12][13] the correlation between these mutations and occult HBV infection remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Occult HBV infection (OBI) was defined by an international workshop held in 2008 as the "presence of HBV DNA in liver (with a viral load of < 200 IU/mL or undetectable HBV DNA in the serum) of individuals testing hepatitis B surface antigen negative by currently available assays" (6)(7)(8). The prevalence of OBI carriers was shown to be more prominent since the introduction of HBV DNA nucleic acid testing (NAT) in blood transfusion centers across all continents with yield varying from 0.1% to 4.16% (2)(3)(4)(5)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Occult HBV infection initially described in the late 1970 by Tabor et al [10] is characterized by the presence of HBV DNA in blood or tissues with undetectable HBsAg, with or without antibodies to hepatitis B core (antiHBc) or hepatitis B surface (anti-HBs), outside the pre seroconversion window period [11,12] . Detection of OBI requires assays of the highest sensitivity and specificity with a lower limit of detection of less than 10 IU/mL for HBV DNA and < 0.1 ng/mL for HBsAg [13] .…”
Section: Introductionmentioning
confidence: 99%